Character Building for Santri Leadership in Modern Islamic Boarding Schools: Pembentukan Karakter Kepemimpinan Santri di Pesantren Modern - Yoshy Randa Siregar; Enny Nazrah Pulungan (Academia Open, 2025)
Background (General): Islamic boarding schools (pesantren) are central institutions in Indonesia’s educational landscape, known not only for religious teaching but also for character development. Background (Specific): Modern pesantren integrate general and religious education with structured mentoring to cultivate leadership among students (santri). Knowledge Gap: Previous studies often examined isolated aspects of leadership training, such as organizational roles or public speaking, but little is known about how pesantren holistically combine education, discipline, and role modeling to form leadership character. Aim: This study investigates the role of Pondok Pesantren Modern Darul Arafah Raya in shaping santri leadership character, along with its supporting and inhibiting factors. Results: Using a descriptive qualitative approach through observation, interviews, and documentation, findings reveal that leadership formation occurs through student organizations, ustaz role models, disciplined boarding routines, and structured public speaking training. Despite initial challenges—such as lack of confidence, time management, and external influences—progressive mentoring significantly improved students’ responsibility, communication, and confidence. Novelty: Unlike prior research, this study demonstrates how pesantren’s integrated system—spiritual, academic, and organizational—collectively fosters leadership qualities. Implications: The findings affirm that modern pesantren are strategic educational models for producing leaders who are intellectually competent, morally upright, and socially responsible, ready to face contemporary challenges.Highlight : Modern Islamic boarding schools shape the leadership of students through organization, exemplary behavior, and discipline. Supporting factors include gradual guidance, the role of teachers, and a conducive environment. Obstacles arise from the students' backgrounds, boredom, time management, and outside influences. Keywords : Islamic boarding schools, character, leadership, students, education